2021
DOI: 10.1021/acs.jpcb.1c01997
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Fibril Formation Caused by Mechanical Shock and Cavitation

Abstract: Cavitation can occur when liquids are exposed to pressure waves of sufficient amplitude, producing rapidly expanding and collapsing gas bubbles that generate localized regions of high energy dissipation. When vials containing insulin were subjected to mechanical shock or when ultrasound was applied to the vials, the resulting cavitation events induced formation of insulin amyloid fibril nuclei that were detected by transmission electron microscopy and quantified by fluorescence spectroscopy following staining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Besides dehydration of adsorbed proteins, other effects of agitation resulting from a dynamic airliquid interface have been frequently suggested to trigger protein aggregation: for instance, foaming is known for its detrimental effects on the stability of proteins [42,43]. Moreover the formation of cavitation bubbles by ultra-sonication has been proposed as a primary nucleationtriggering mechanism [26,44,45]. In our case however, neither of the experimental setups resulted in the formation of foaming nor bubbles.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Besides dehydration of adsorbed proteins, other effects of agitation resulting from a dynamic airliquid interface have been frequently suggested to trigger protein aggregation: for instance, foaming is known for its detrimental effects on the stability of proteins [42,43]. Moreover the formation of cavitation bubbles by ultra-sonication has been proposed as a primary nucleationtriggering mechanism [26,44,45]. In our case however, neither of the experimental setups resulted in the formation of foaming nor bubbles.…”
Section: Discussionmentioning
confidence: 55%
“…Its stability has been extensively studied in various conditions (low pH and high temperature [22], physiological conditions [23]). It has also been known for a long time for its aggregation into amyloid fibrils [24] and its instability in medical devices [25,26]. At physiological pH and temperature, it has been shown by Sluzky and colleagues [23] and then by Ballet and coworkers [27] that a solution of human insulin can aggregate in the presence of a hydrophobic surface only when the solution is agitated.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism which leads insulin to form fibrils is a physical process that follows a sigmoidal curve, with a lag phase, rapid growth, and a plateau ( Figure 2 ). The mechanism of insulin’s fibril formation has been proposed to consist of three main reactions: nucleation, growth, and precipitation [ 43 ]. Nucleation consists of the formation of stable nuclei, and it is viewed as the assembly process toward an organized structure.…”
Section: Insulin Fibrillationmentioning
confidence: 99%
“…In these conditions, the meniscus’s continuous movement during agitation leads to the generation of transiently dry areas, causing the partial dehydration of adsorbed proteins that may then aggregate more easily [ 52 ]. Similarly, fibrillation is promoted by mechanical shocks and cavitation, which can occur when pressure waves of sufficient amplitude produce gas bubbles within liquids that rapidly expand and collapse, generating localized regions of high energy dissipation [ 43 ]. Finally, a recent study showed that increasing interfacial shear rate produces a monotonic increase in the fibrillation rate, with a monotonic decrease in fibrillation time [ 53 ].…”
Section: Insulin Fibrillationmentioning
confidence: 99%